2012
DOI: 10.4081/ejh.2012.e7
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-d activity in rat thymus after the application of retinoid acid

Abstract: The aim of this work was to determine the localization of nicotinamide-adenine dinucleotide phosphate-diaphorase (NADPH-d) activity as the marker for synthesis of nitric oxide synthase (NOS) in the rat thymus after the application of retinoid acid (RA) on 1st, 7th, 14th and 21st days of gestation. The given results can build the basis for understanding of the role of NOS in rat thymus. NADPH-d positive cells were represented with dark-blue color and were localized on corticomedullar junction of the thymus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Although the function of NO in the thymus and spleen has not been demonstrated, the findings of the current study indicate that there is an association between the immunological effects induced by BetA. The major effect of BetA-induced NO appears to be involved in maintenance of the immune system ( 38 40 ) and the current results support other reports in which the presence of NO was demonstrated in the immune system ( 33 , 41 ).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Although the function of NO in the thymus and spleen has not been demonstrated, the findings of the current study indicate that there is an association between the immunological effects induced by BetA. The major effect of BetA-induced NO appears to be involved in maintenance of the immune system ( 38 40 ) and the current results support other reports in which the presence of NO was demonstrated in the immune system ( 33 , 41 ).…”
Section: Discussionsupporting
confidence: 83%
“…Although NO is less active in cells from normal mice ( 43 ), a spleen cell subpopulation produces enough NO during an in vitro immune response to completely prevent multiplication of T cells ( 44 , 45 ). Similarly, previous studies have demonstrated that a wide range of potential immunomodulatory functions may be expected for NO in the thymus, including the following: Induction of tolerance, restriction of major histocompatibility complex, lymphocyte trafficking and regulation of thymic endocrine output ( 33 , 36 , 37 , 42 ). Furthermore, if there are effects or changes in the cells due to BetA treatment, it is assumed that NO may be produced to perform its regulatory roles in the cells of these immune organs.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations